Effect Of Functional Endoscopic Sinus Surgery To The Flow Behavior In Nasal During Resting Breathing Condition - Mokhtar, Nur Hazwani; Md Jahan, Al-Muttaqin; Osman, Kahar; Abdul Kadir, Mohammed Rafiq; Wan Abdullah, Wan Ahmad Kamil; Haron, Juhara (2012)
Functional endoscopic sinus surgery is a surgery to remove uncinate process in order to restore sufficient sinus ventilation and drainage in nasal. However, there were a few cases wit11 side effects such as facial pain, reduction in sense of smell and sinusitis reoccurrence of infection. In this study, the effect of uncinate process removal is investigated. Images of the model were done through computational technique and then the flow was simulated to predict the effect of the removal. Inhalation processes with resting breathing condition were modeled. The results &how that smooth flow was observed at nasal area which indicates successful surgical process. However for post FESS model the result shows that the possibilities of sinusitis reoccurrence of infection were high. Finally, velocity profile in the olfactory area show non-favorabIe flow condition for effective smell senses.